2021
DOI: 10.1063/pt.3.4656
|View full text |Cite
|
Sign up to set email alerts
|

Science and technology of the Casimir effect

Abstract: Caused by simple fluctuations in space, the Casimir effect may validate theories of the cosmological constant and allow for measurements of ultrasmall magnetic fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…This suggests the presence of something, a state of empty-fullness that Aristotle called the plenum. The most commonly cited example in support of the fullness of the quantum vacuum and zero-energy state is the Casimir effect [21,22]. Two uncharged conductive plates are placed in a vacuum in nanometer proximity to each other.…”
Section: Quantum Vacuum and Aethermentioning
confidence: 99%
“…This suggests the presence of something, a state of empty-fullness that Aristotle called the plenum. The most commonly cited example in support of the fullness of the quantum vacuum and zero-energy state is the Casimir effect [21,22]. Two uncharged conductive plates are placed in a vacuum in nanometer proximity to each other.…”
Section: Quantum Vacuum and Aethermentioning
confidence: 99%
“…Fourier transforming (27) and (28), both in time and space, one can relate the current density j(ω, k) = en 0 v(ω, k) to the electric field E(ω, k), thus obtaining the conductivity tensor and, ultimately the dielectric function where at the last stage the lattice contribution ε L (ω) has been added. 29) is the Debye screening radius.…”
Section: Drude Model With Spatial Dispersionmentioning
confidence: 99%
“…Devices in which forces between mechanical components are exchanged via the mediation of vacuum fluctuations could find application in those research fields where high sensitivity is required, such as in the search for gravitational waves [12] and dark matter [13]. They could be used in quantum metrology and quantum sensing [14] and, in the near future, could serve as actuators of nanoscale motion, for manipulating objects as small as nanowires, quantum dots, or even living organisms such as viruses and bacteria in biological applications [15]. Recent proposals have also shown that nanometric system could be used to realize mechanically based quantum bit [16] for quantum information and quantum computing.…”
Section: Introductionmentioning
confidence: 99%